2013
DOI: 10.3892/etm.2013.1302
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic comparison of the vasorelaxant compound ferulic acid following the administration of Guanxin II to healthy volunteers and patients with angina pectoris

Abstract: Coronary heart disease (CHD) is the leading cause of mortality worldwide. The Chinese medicinal formula Guanxin II has been shown to have a favorable effect in the attenuation of angina. The aim of this study was to compare the pharmacokinetics of ferulic acid (FA), which is a vasorelaxant compound present in Guanxin II, in healthy volunteers and patients with angina pectoris following the administration of Guanxin II. Ex vivo experiments were performed in order to investigate the vasorelaxant effect of FA on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…It is positioned on chromosome 10 in rats while chromosome 11 and chromosome 17 are for mice and human beings, respectively (Maharshak et al, 2013). MiR-132 has tissue specificity and has high expressions in nerve- related tissues (Wang et al, 2013). It participates in axon growth, proliferation and differentiation of synapsis and formation of nerve tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is positioned on chromosome 10 in rats while chromosome 11 and chromosome 17 are for mice and human beings, respectively (Maharshak et al, 2013). MiR-132 has tissue specificity and has high expressions in nerve- related tissues (Wang et al, 2013). It participates in axon growth, proliferation and differentiation of synapsis and formation of nerve tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized early in 1993 (Zhang et al, 2014a). It is single structured and participates in essential biological functions such as cell development, apoptosis and metabolism, etc (Wang et al, 2013). As the important role of microRNA in some tumors has been confirmed, many scholars conducted initial studies on relationship between microRNA and occurrence, development and metastasis of liver cancer (Toffanin et al, 2011;.…”
Section: Article Infomentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have been performed to date. Li et al [21] recently reported the pharmacokinetic parameters of ferulic acid in healthy volunteers. The results showed that SF was absorbed at a fast rate and rapidly eliminated (t 1/2 21 min).…”
Section: Sodium Ferulate Biotransformation In Humanmentioning
confidence: 99%
“…It has the effect of anti-myocardial ischemic injury and inhibiting platelet aggregation. 7,8 JZGXP is made of Chinese herbal medicines such as red peony root, Salvia miltiorrhiza, chuanxiong, safflower and Lignum Dalbergiae Odoriferae. They have the function of promoting blood circulation and removing blood stasis and are used for chest sputum caused by internal hemorrhage.…”
Section: Introductionmentioning
confidence: 99%